A Study of Macroalgae-derived Cellulosic Nanomaterials and Janus Graphene Oxide for Enhanced Oil Recovery - Tiong Chiong Yuh, Adrian (Curtin University, 2023)
The macroalgae Eucheuma cottonii (EC) has been widely cultivated in Sabah, Malaysia, for carrageenan extraction. This project utilized the two main components of EC, cellulose and carrageenan, for various investigations. Cellulose was extracted for nano-cellulose production, and carrageenan was investigated as a template for Janus graphene oxide synthesis. Nano-cellulose and Janus graphene oxide were experimentally investigated for enhanced oil recovery potential. Up to 22.96 % of additional oil recovery was attained.